Active deformation near the Nicoya Peninsula, northwestern Costa Rica, between 1996 and 2010 : Interseismic megathrust coupling - Newman, Andrew V. (2013)
We use campaign and continuous GPS measurements at 49 sites between 1996 and 2010 to describe the long-term active deformation in and near the Nicoya Peninsula, northwestern Costa Rica. The observed deformation reveals partial partitioning of the Cocos-Caribbean oblique convergence into trench-parallel forearc sliver motion and less oblique thrusting on the subduction interface. The northern Costa Rican forearc translates northwestward as a whole ridge block at 11 ± 1 mm/yr relative to the stable Caribbean. The transition from the forearc to the stable Caribbean occurs in a narrow deforming zone of ∼16 km wide. Subduction thrust earthquakes take 2/3 of the trench-parallel component of the plate convergence; however, surface deformation caused by interseismic megathrust coupling is primarily trench-normal. Two fully coupled patches, one located offshore Nicoya centered at ∼15 km depth and the other located inland centered at ∼24 km depth, are identified in Nicoya with the potential to generate an Mw 7.8 1950-type earthquake. Another fully coupled patch SE of Nicoya coincides with the rupture region of the 1990 Nicoya Gulf earthquake. Interface microearthquakes, non-volcanic tremor, low-frequency earthquakes, and transient slow-slip events generally occur in the intermediately to weakly coupled regions.